The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.bbamem.2009.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Integrin reconstituted in GUVs: A biomimetic system to study initial steps of cell spreading

Abstract: A novel in vitro membrane system mimicking the first steps of integrin-mediated cell spreading has been developed and characterized. We have reconstituted the transmembrane alpha(IIb)beta(3) integrin into giant unilamellar vesicles (GUVs). The reconstitution process has been validated by analyzing protein incorporation and biological activity by checking the specific interaction of GUVs containing integrin with quantum dots (QD) or surfaces coated with the integrin receptor tri-peptide RGD.(1) The spreading dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 45 publications
3
63
0
4
Order By: Relevance
“…The method has already been applied to reconstitute Cx26 in GUVs (24). To obtain larger protein amounts, Streicher et al (46) reconstituted integrins into GUVs by briefly drying preformed proteoliposomes on ITO coated-glass slides. However, the drying process can cause inactivation of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…The method has already been applied to reconstitute Cx26 in GUVs (24). To obtain larger protein amounts, Streicher et al (46) reconstituted integrins into GUVs by briefly drying preformed proteoliposomes on ITO coated-glass slides. However, the drying process can cause inactivation of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers are now going a step further and beginning to create artificial cells in the form of liposomes containing lipid membrane-bound receptors, such as integrin. 95 These synthetic cells have already been utilized to study receptormediated spreading and adhesion 95,96 and actin-loaded liposomes were shown to drive actin polymerization to spontaneously form cytokinetic rings. 97 These synthetic "cells" have huge potential and could help to answer many complex biological questions in several fields of life sciences such as virology (in particular viral entry), and loaded liposomes have already been adapted for clinical applications in drug delivery.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…However, work in this area is progressing and has yielded promising results. [108][109][110][111][112] For instance, the functional reconstitution of a voltage-gated potassium channel and α bII β 3 integrin in giant unilamellar vesicles was recently described. 108,110 The potential advantages of the incorporation of several exosomal proteins in exosome mimetics are discussed below.…”
Section: Lipidsmentioning
confidence: 99%